(untitled) (Plant Tissue Culture and Biotechnology, 2013)
An efficient protocol was developed for highly regenerative capacity from leaf explant of Withania somnifera (L.) Dunal ? an endangered medicinal plant. Calli were regenerated from four different explants like leaves, cotyledons, hypocotyls and epicotyls. MS supplemented with different concentrations of 2,4?D, BAP and NAA were used. The calli (94.33 ± 1.20%) were obtained from the leaf explant in 2,4?D 3.0 mg/l. The highest number of multiple shoots (85.67 ± 0.88%) were obtained from the leaf callus at 4.0 mg/l BAP. Shootlets forming calli were transferred to the rooting medium containing 10.0 mg/l NAA to produce multiple roots (89.33 ± 0.88%). The regenerated rooted shootlets were transferred to small polythene bags, which contain a sterilized cow?dung, sand and red soil (1 : 2 : 3) and kept in a mist house. After acclimation in the mist house the regenerated plantlets were hardened in the greenhouse and transferred to soil, which showed 85% survival rate. This new protocol was standardized for easy mass propagation of W. somnifera using leaf explant. Plant Tissue Cult. & Biotech. 23(1): 79?85, 2013 (June) DOI: http://dx.doi.org/10.3329/ptcb.v23i1.15564